CONDITIONS FOR IMPROVING THE EFFECTIVENESS OF TEAMWORK IN MODERN REALITIES - SAZONOVA, Tetiana; GRODZINSKA, Anastasia; YALOVEGA, Denis; VOLOSHCHUK, Vladislav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the consideration of the features of the implementation of team management in general and taking into account the specifics of the functioning of the enterprise in the modern domestic environment. The features of the functioning of enterprises under martial law and changes in the personnel management system of enterprises associated with these features are determined: restrictions on freedom of action, decisions; functioning in emergency circumstances; instability of the economic and social situation; priority of security, stability is a priority over growth. A feature of team management in modern domestic realities is also the specificity of the motivation system and opportunities for its development. Ways to improve interaction in the team are proposed: goal setting, communication and cooperation, development of relationships. It is important to note that at each stage there is activity and motivation not only of the manager, leader, but all team members should be involved - their strengths, competence, experience. The need to ensure psychological safety for the personnel of modern enterprises is emphasized, which is associated with significant economic, social and physical dangers and stressfulness of the external environment. A sense of psychological safety in a team increases its productivity, and in fact, it is four times more important than any other factor in shaping productivity. Psychological safety ensures that team members feel comfortable asking for help, offering it, or refusing it. Proposed key elements that form psychological safety in a team, including: team leader, trust and respect, organizational support, team habits, interaction practices. It is also stated that effective relationships and psychological safety, trust are formed by constructive criticism, which is an integral element of team interaction, but must meet the requirements of efficiency, constructiveness and environmental friendliness. The need for building effective relationships in the collective in general and the team, in particular, compliance with the rules of constructive dialogue: constant search for potential for unity and definition of common goals and interests; ask colleagues for advice in order to gain their support; ask questions, and not just state facts, thereby finding out the interlocutor's motives, etc.
Keywords: team; team management; personnel; psychological danger; constructive criticism; dialogue